Polysialic acid restrains inflammatory monocyte maturation - Passos, Ingredy; Peschke, Benjamin; Gandhi, Shrey; Derdelinckx, Judith; Müller-Miny, Louisa; Neumann, Harald; Lünemann, Jan D.; Keller, Christian W. (Frontiers in Immunology, 2025)
Sialic acids are widely distributed monosaccharides in the central nervous system (CNS), where they are predominantly found as terminal sialic acid residues, as well as in di-, oligo-, and polysialic forms on the glycocalyx, collectively contributing to the development, resilience, and long-term integrity of the CNS. Harnessing sialic acid–binding immunoglobulin-like lectin (Siglec) receptors by α2.8-linked polysialic acids has been shown to modulate immune responses. In this study, murine and human monocytes were exposed to α2.8-linked low molecular weight polysialic acid (α2.8-polySIA) in vitro, followed by phenotypic, functional, and transcriptomic analyses using flow cytometry and RNA sequencing; therapeutic efficacy was assessed in mice with experimental autoimmune encephalomyelitis (EAE), a pre-clinical model of multiple sclerosis (MS). Here, we report that α2.8-polySIA inhibits toll-like receptor-induced phenotypical and functional maturation of murine and human monocytes into pro-inflammatory effector cells equipped with operational antigen-presenting machinery. Moreover, RNA sequencing analyses revealed a shift towards a regulatory phenotype in human myeloid cells exposed to α2.8-polySIA. Finally, therapeutic treatment with α2.8-polySIA led to a milder disease course in EAE mice. Thus, by tuning myeloid cell phenotype in vivo, the therapeutic application of polysialic acid may offer a novel approach to modulate myeloid-driven inflammation in CNS autoimmunity.